Nonprofit Organizations’ Financial Obligations and the Paycheck Protection Program - Neely, Daniel G.; Saxton, Gregory D.; Wong, Paul A. (Management Science, 2023)
We examine nonprofit organizations’ involvement in the Paycheck Protection Program (PPP). The PPP provided participants with forgivable loans to pay employee salaries, increasing participants’ financial flexibility during the pandemic. We examine the associations between nonprofits’ prepandemic financial obligations (e.g., long-term debt and donor-restricted net assets) and PPP participation and participants’ loan characteristics. First, we find nonprofit organizations participated at a lower rate than other small business industries and that nonprofits with greater financial obligations were more likely to participate in the program. Second, we find financial obligations were positively associated with the loan amount received as a percentage of total payroll costs. Last, although approximately 11% of nonprofits failed to obtain loan forgiveness, we find nonprofits with restricted net assets were more likely to have their loans forgiven. Our results suggest nonprofits with greater debt and donor obligations used the PPP to increase their financial flexibility. This paper was accepted by Ranjani Krishnan, accounting. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4804 .